Representasi Makna Kehidupan Melalui Perjalanan Tokoh Dalam Novel Perahu Kertas Karya Dewi Lestari - Yola Putri; Yola Aulia Putri; Nadyla Zahra; Abdurahman . (CV. ITTC INDONESIA, 2026)
This study aims to describe the representation of the meaning of life through the characters' journeys in the novel Perahu Kertas by Dewi Lestari. The research employs a qualitative descriptive method with an objective approach. The primary data source is the novel Perahu Kertas. Data collection techniques involve intensive reading, noting relevant excerpts, and classifying data according to the research focus. Data analysis techniques include data reduction, data presentation, and conclusion drawing. The findings reveal that the meaning of life is represented through the struggle to achieve dreams, the courage to be oneself, the process of maturation through failure, the importance of social support, the tension between idealism and reality, and the belief that time plays a role in leading individuals to their life purposes. The characters' journeys demonstrate that life does not always go according to plan, yet every experience holds valuable lessons that shape human character.